RANCANG BANGUN APLIKASI TRACING DAN MONITORING REALISASI RENCANA ANGGARAN BIAYA PROYEK PADA PT SUCOFINDO CABANG SURABAYA - Evanda, Graciela; Rahmawati, Endra; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
PT Superintending Company of Indonesia (PT Sucofindo) is aÂ  inspection company. In its business, PT Sucofindo does budgeting after receiving a pre-order or work contract by making a Budget Plan (RAB) and proceeding with the execution of the work. Where there is budgeting, there is realization. The recording of budget realization is still using excel with different files and input into the central ERP. Some of the problems that occurred related to RAB realization were: difficult to trace and to know the details of realization costs per project. As a result, there is no cost control so sometimes the realization exceeds the budget (there is a cost overrun). The non-conformance of the target budget plan will have an impact on budgeting the next year's project costs, decision-making errors when evaluating project budget performance, not achieving the annual budget plan, etc. To overcome these problems, a "tracing and monitoring application for the realization of the project's Budget realization" was made which recorded the realization of the budget for each project so that it could assist the company in controlling the cost of project realization in accordance with the RAB made.